Measuring subnational democracy: toward improved regime typologies and theories of regime change. Issue 1 (2nd January 2018) - McMann, Kelly M.
ABSTRACT: Social scientists have been limited in their work by the paucity of global time series data about subnational institutions and practices. Such data could help scholars refine regime typologies, improve theories of democratization and regime change, better understand subnational democracy, and illuminate issues of development, conflict, and governance. This article addresses the lack of data by introducing 22 subnational measures from a new dataset, Varieties of Democracy. Validity tests demonstrate that the measures' strengths outweigh their weaknesses. The measures excel in covering all subnational levels for most countries, capturing different elements of subnational elections, and including a variety of dimensions of elections and civil liberties. The measures also offer unmatched global and temporal coverage. The article demonstrates how these strengths can provide scholars with the benefits described above.